Physical and chemical aspects at the interface and in the bulk of CuInSe2-based thin-film photovoltaics. Issue 3 (22nd December 2021) - Ishizuka, Shogo; Nishinaga, Jiro; Beppu, Kosuke; Maeda, Tsuyoshi; Aoyagi, Fuuka; Wada, Takahiro; Yamada, Akira; Chantana, Jakapan; Nishimura, Takahito; Minemoto, Takashi; Islam, Muhammad Monirul; Sakurai, Takeaki; et al.
Abstract : Technical issues which remain in CuInSe2 -based solar cells are reviewed. A study of single-crystalline Cu(In, Ga)Se2 film devices, carrier recombination analysis, and effects of alkali-metal doping and silver-alloying are particularly focused on. Abstract : Chalcopyrite CuInSe2 (CISe)-based thin-film photovoltaic solar cells have been attracting attention since the 1970s. The technologies of CISe-based thin-film growth and device fabrication processes have already been put into practical applications and today commercial products are available. Nevertheless, there are numerous poorly understood areas in the physical and chemical aspects of the underlying materials science and interfacial and bulk defect physics in CISe-based thin-films and devices for further developments. In this paper, current issues in physical and chemical studies of CISe-based materials and devices are reviewed. Correlations between Cu-deficient phases and the effects of alkali-metals, applications to lightweight and flexible solar minimodules, single-crystalline epitaxial Cu(In, Ga)Se2 films and devices, differences between Cu(In, Ga)Se2 and Ag(In, Ga)Se2 materials, wide-gap CuGaSe2 films and devices, all-dry processed CISe-based solar cells with high photovoltaic efficiencies, and also fundamental studies on open circuit voltage loss analysis and the energy band structure at the interface are among the main areas of discussion in this review.